2010
DOI: 10.4102/curationis.v33i2.1100
|View full text |Cite
|
Sign up to set email alerts
|

An information system to manage the rollout of the antiretroviral treatment programme in the Free State

Abstract: Curationis 33 (2): 60-68The Acquired Immune Deficiency Syndrome epidemic, caused by the Human Immu nodeficiency Virus, is a global crisis which threatens development gains, economies, and societies. Within sub-Saharan Africa, where the epidemic began the earliest and the HIV prevalence is the highest, African countries have death rates not seen be fore. In South Africa the epidemic has a devastating impact which creates profound suffering on individuals and their families, and the impact on the socio-economic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Three studies conducted on HIV/AIDS Management systems in South Africa (Kotze and McDonald, 2010), Rwanda (Amoroso et al, 2010) and Haiti (Fraser et al, 2004) showed improved monitoring and evaluation of antiretroviral data and HIV/AIDS treatment across the three countries (Fraser et al, 2004;Merrell et al, 2004, Amoroso et al, 2010. In Rwanda, the use of detailed HIV/AIDS and TB computerized data facilitated patient follow up, improved data accessibility and quality (92 percent reduction in systematic errors) and improved patient care (Amoroso et al, 2010).…”
Section: Evaluation Of Effectiveness Of Emrs In Data Managementmentioning
confidence: 99%
“…Three studies conducted on HIV/AIDS Management systems in South Africa (Kotze and McDonald, 2010), Rwanda (Amoroso et al, 2010) and Haiti (Fraser et al, 2004) showed improved monitoring and evaluation of antiretroviral data and HIV/AIDS treatment across the three countries (Fraser et al, 2004;Merrell et al, 2004, Amoroso et al, 2010. In Rwanda, the use of detailed HIV/AIDS and TB computerized data facilitated patient follow up, improved data accessibility and quality (92 percent reduction in systematic errors) and improved patient care (Amoroso et al, 2010).…”
Section: Evaluation Of Effectiveness Of Emrs In Data Managementmentioning
confidence: 99%